The Impact of Social Media Marketing Activities on Brand Awareness and Sales Performance of Small and Medium Enterprises: Evidence from Indonesia - Ahmad Kamaludin; Ikhsan Nendi (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid proliferation of social media platforms has fundamentally transformed the marketing landscape for Small and Medium Enterprises (SMEs) in Indonesia, creating both opportunities and challenges in brand building and revenue generation. Objective: This study examines how five social media marketing activity (SMMA) dimensions (content quality, posting frequency, influencer collaboration, community interaction, and platform selection) shape brand awareness, and how brand awareness converts into sales performance through brand trust. Methods: This study employed a qualitative design. Twenty SME owners and managers were purposively selected across five Indonesian provinces (West Java, DKI Jakarta, East Java, Yogyakarta, and Bali) and five sectors. Semi-structured interviews of 45–90 minutes were conducted over sixteen weeks and triangulated with document analysis of 20 business accounts and five field observations. Transcripts were coded in NVivo 12 Pro using Braun and Clarke’s six-phase reflexive thematic analysis, followed by axial and selective coding and member checking with eight participants. Results: The findings indicate that consistent and targeted social media marketing activities significantly enhance brand visibility, consumer engagement, and sales conversion. Instagram and TikTok emerged as the most impactful platforms, while content quality, posting frequency, and micro-influencer collaboration were the decisive success factors. Brand trust, rather than recognition alone, converted awareness into revenue. Conclusion: This study contributes theoretical and practical insights into the SMMA–brand awareness–sales performance nexus within emerging economy contexts, offering actionable implications for SME owners, policymakers, and digital marketing practitioners in Indonesia.